Droplet-assisted microfluidic fabrication and characterization of multifunctional polysaccharide microgels formed by multicomponent reactions - Hauck, Nicolas; Seixas, Nalin; Centeno, Silvia P.; Schluelsser, Raimund; Cojoc, Gheorghe; Mueller, Paul; Guck, Jochen; Woell, Dominik; Wessjohann, Ludger A.; Thiele, Julian (Polymers, 2018)
Polysaccharide-based microgels have broad applications in multi-parametric cell cultures, cell-free biotechnology, and drug delivery. Multicomponent reactions like the Passerini three-component and the Ugi four-component reaction are shown in here to be versatile platforms for fabricating these polysaccharide microgels by droplet microfluidics with a narrow size distribution. While conventional microgel formation requires pre-modification of hydrogel building blocks to introduce certain functionality, in multicomponent reactions one building block can be simply exchanged by another to introduce and extend functionality in a library-like fashion. Beyond synthesizing a range of polysaccharide-based microgels utilizing hyaluronic acid, alginate and chitosan, exemplary in-depth analysis of hyaluronic acid-based Ugi four-component gels is conducted by colloidal probe atomic force microscopy, confocal Brillouin microscopy, quantitative phase imaging, and fluorescence correlation spectroscopy to elucidate the capability of microfluidic multicomponent reactions for forming defined polysaccharide microgel networks. Particularly, the impact of crosslinker amount and length is studied. A higher network density leads to higher Young's moduli accompanied by smaller pore sizes with lower diffusion coefficients of tracer molecules in the highly homogeneous network, and vice versa. Moreover, tailored building blocks allow for crosslinking the microgels and incorporating functional groups at the same time as demonstrated for biotin-functionalized, chitosan-based microgels formed by Ugi four-component reaction. To these microgels, streptavidin-labeled enzymes are easily conjugated as shown for horseradish peroxidase (HRP), which retains its activity inside the microgels.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Droplet microfluidics; Multicomponent reaction; Passerini three-component reaction; Polysaccharide microgels; Ugi four-component reaction